Estudo do processo de liberação lenta de fertilizantes a partir de nanocompósitos de matriz ureia - Pereira, Elaine Inácio (Universidade Federal de São Carlos, 2014)
The efficient use of fertilizers, especially nitrogen ones, is essential and strategic for the obtention of maximum economic crop yields and to minimize the loss of nutrients into the environment. Among the technologies that can possibly contribute to the effective use of fertilizers and, consequently, with solutions to the environmental problems caused, are the systems of slow or controlled release; among these systems, are the ones based on the association of lamellar materials and/or polymers to fertilizers. Thus, the objective of this study was to analize the diffusion behavior of urea, when associated with an exfoliated clay mineral (montmorillonite MMT) in its structure, with or without the presence of interface-modifying polymers thus obtaining a nanocomposite. Manufacturing process used- the extrusion of a plastic mixture - is simple and can be scaled up, allowing granule production without high costs. In the first part, nanocomposites were obtained by an extrusion process, from only MMT and the fertilizer urea (nitrogen source) at different mass ratios (1:1; 1:2 and 1:4). From the results of the characterization of these materials, it is possible to observe that urea served as a dispersant for MMT, requiring lower levels of water for processing, allowing the obtention of granular materials, by extrusion, with a mechanical strength superior to the pure urea granule. Furthermore, the presence of MMT generates a retaining means for urea (Ur), through which it has to spread, acting as a physical barrier, observed by the slow release of urea in water. In the second part of the study, two other groups of nanocomposites were prepared, using the ratio 1:4 MMT/urea, adding different percentages (1, 2 and 4% in relation to the total weight) of two different polymers: polyacrylamide hydrogel (HG) and polycaprolactone (PCL). The addition of HG (hydrophilic) to the abovementioned composite generated a new interface between these materials, with stronger interactions, resulting in a significant improvement in the mechanical strength of the mixture, besides presenting a slower kinetic release behavior of urea, when compared to the composite 1:4 MMT/Ur. On the other hand, the presence of PCL produced composites with a more segregated porous structure, irregular surface morphology, interfered with the diffusion process of urea, but did not improve significantly the resistance of the mixture. Composites were also able to reduce the emission of N2O, when applied to a soil planted with wheat, showing, indirectly, an effect on the diffusion of urea to the soil. In the end, a test was conducted for the determination of mineralizable nitrogen in an incubated soil, which showed a mineralization comparable with the pure urea for all nanocomposites, but a representative difference between the tested materials was not observed. This indicates that further studies are needed to better the comprehension of these results.
Study of the slow release fertilizer process from nanocomposite of urea matrix
Keywords: Fertilizantes nitrogenados; Ureia; Montmorilonita; Processo de extrusão; Liberação lenta; CIENCIAS EXATAS E DA TERRA::QUIMICA